DRUGS THAT AFFECT THE CARDIOVASCULAR SYSTEM - SILVA, VIVIANE APARECIDA; PEREIRA, ERICA RENATA GONÇALVES; MATA, GABRIELLY BESSA DA; FILGUEIRA, KADIJA MENDES; MATIAS, MARCELLA VITORIA; CAVALCANTE, MARIA VITORIA OLIVEIRA; NEVES, THAYS KAROLINY SANTOS; FILHA, ANA JULIA ANDRADE BATISTA (CIPEEX, 2025)
The cardiovascular system is responsible for distributing blood, nutrients, and oxygen to the body, and its dysfunction is associated with highly prevalent diseases such as hypertension, heart failure, heart attack, and stroke. This study aims to review the main drugs used in the treatment of cardiovascular diseases and their clinical applications. A scientific literature analysis was performed using the PubMed, SciELO, and LILACS databases. The inclusion criteria involved articles published between 2015 and 2024, available in Portuguese, English, and Spanish, with access to the full text and specifically addressing the use of drugs in the treatment of cardiovascular diseases. Duplicate studies, studies with insufficient samples, non-systematic reviews, and articles that did not present relevant clinical information about the drugs were excluded. The review was descriptive and didactic in nature, involving drugs such as antihypertensive agents, statins, anticoagulants, and beta-blockers. Antihypertensive drugs are classified as: diuretics, adrenergic blockers, calcium channel blockers, direct vasodilators, and angiotensin-converting enzyme (ACE) inhibitors, each with distinct mechanisms. Statins are effective in reducing LDL cholesterol and preventing atherosclerotic events. Anticoagulants are essential in the prophylaxis and treatment of thrombosis and embolism. Beta-blockers are widely used in hypertension, arrhythmias, heart failure, and anxiety control. Understanding the mechanisms of action and clinical indications of cardiovascular drugs is essential for the proper management of major cardiovascular diseases, contributing to the reduction of morbidity and mortality rates associated with these conditions.